Internationalization Models for Colombian SMEs (2019)
Small and Medium sized Enterprises (SME´s) are fundamental actors in Colombian economy, as they are in other countries. Fast paced globalization imposes challenges to these companies in terms of the new opportunities and threats arising within the current competitive environment. For the SME entrepreneur, comprehending the theories on internationalization processes –how they take place, what their drivers are, and which models could be the fittest to expand his operations in international markets–, are key questions he must answer in order to survive, grow or increase the profitability of the organization. Management skills required to pursue such task are one of the most critical success factors for SME´s, and therefore, they become a critical focus on which deeper studies and discussions shall be encouraged